Laboratory efficacy of Bactivec® and Griselesf® biolarvicides used for large-scale larviciding in Tanzania - Gavana, Tegemeo; Kailembo, Denis; Machange, Jane; Michael, Venance; Swai, Kyeba; Odufuwa, Olukayode G.; Tenywa, Frank; Dismas Mwalimu, Charles; Bernard, Jubilate; Lazaro, Samwel; Yoram, Best; Kajange, Stella; et al. (Frontiers in Malaria, 2025)
BackgroundFrom 2022 to 2024, a project piloting large-scale larviciding in Tanzania was implemented in Tanga Region. The project used in-country manufactured biolarvicides, Bactivec® and Griselesf®. This study independently assessed the efficacy of both biolarvicide products to ensure that they represented a good option for scaling up.MethodologyThe study was conducted at Ifakara Health Institute (IHI) in Tanzania. Laboratory-based dose–response experiments were performed using Bactivec® and Griselesf® against laboratory-reared early third instar larvae of Anopheles gambiae sensu stricto, Anopheles arabiensis, Anopheles funestus, Aedes aegypti and Culex quinquefasciatus. Larvae were exposed to various concentrations of Bactivec® and Griselesf®. VectoBac® served as a positive control, and distilled water as a negative control. Twelve replicates per concentration, with 25 larvae per replicate, were tested. Larval mortality was recorded at 24 and 48 hours after exposure to Bactivec® and Griselesf®, respectively. Probit regression analysis was used to determine the lethal concentration (LC50 and LC90) values.ResultsBactivec® demonstrated similar LC50 values across all species, ranging from 0.0122 mg/mL (95% CI: 0.0114–0.0130) for An. gambiae s.s. to 0.0155 mg/mL (95% CI: 0.0147–0.0163) for An. funestus. LC90 varied slightly, with An. arabiensis being the most susceptible at 0.0217 mg/mL (95% CI: 0.0202–0.0233), and An. gambiae s.s. the least at 0.0330 mg/mL (95% CI: 0.0298–0.0363). Griselesf® showed greater variation, with LC50 ranging from 0.0130 mg/mL (95% CI: 0.0124–0.0136) for An. gambiae s.s. and 0.0212 mg/mL (95% CI: 0.0199–0.0226) for An. arabiensis. Similarly, the LC90 for Griselesf® also varied, being the lowest for An. gambiae s.s., 0.0235 mg/mL (95% CI: 0.0219–0.0252) and the highest for An. arabiensis, 0.0609 mg/mL (95% CI: 0.0548–0.0669). Ae. aegypti was not susceptible to Griselesf® at the concentrations tested. The LC90 observed in this study were below the maximum application rates recommended by the manufacturer but exceeded the minimum application rates for both larvicides.ConclusionThe Tanzanian-made Bactivec® and Griselesf® demonstrated efficacy against multiple species of mosquitoes, when applied according to the manufacturer’s recommendations except for Ae. aegypti, which was not susceptible to Griselesf®. Field applications should use maximum application rates. As Tanzania prepares to expand larviciding nationwide, the availability of these efficacious biolarvicides within the country will enhance both the feasibility and sustainability of the scale-up effort.